Polymerase chain reaction (PCR) for the rapid detection of Salmonella in desiccated coconut (DC) - D. L. Jayaratne; U. N. D. S. Kanakaratne; W. K. N. Shanthichandra (International Coconut Community, 2007)
This study was carried out to develop a polymerase chain reaction (PCR) protocol for the detection of Salmonella in desiccated coconut (DC). For the PCR detection of Salmonella, genomic DNA was extracted using the ‘boiling lyses’ method and the reaction was carried out with Salmonella genus specific primers enabled to amplify 457bp sequence covering invA and invE genes. Samples of DC produced in mills already tested for Salmonella using conventional cultural methods gave identical results with the present PCR method indicating its suitability for adoption in routine testing. The sensitivity checked using DNA extracted from artificially inoculated DC with serially diluted inoculum of Salmonella M1 type showed that the developed PCR method can be used to detect very low levels of contamination of Salmonella as low as 4 CFU/g in DC. The method described here reduces the testing and detection time from 6 days to 24 hours ensuring exporters to obtain Salmonella test reports just prior to shipment.